The Role of the Agricultural Sector on Economic Growth of Donggala Regency - Salsabila, Zoel Daleta; Paembonan, Laendatu; Parinding, Kalvin A.; Yohan, Yohan; Musdayati, Musdayati (Transpublika Publisher, 2025)
The agricultural industry continues to be a significant source of employment in Indonesia, surpassing other sectors in terms of job opportunities. This underscores the importance of the agricultural sector in influencing the country's economy. Similarly, in Donggala Regency, agriculture plays a pivotal role in supporting the local economy. This research aims to assess the agricultural sector's impact on economic development in Donggala Regency. The study utilizes descriptive analysis and formulas to examine growth and contributions. The findings indicate that agriculture is a key sector in Donggala Regency, despite its slower growth rate compared to other sectors, as it makes the most significant contribution to the region's economic growth. For this reason, the result suggest that it is imperative for policymakers to focus on enhancing the agricultural sector by making strategic investments in technology, infrastructure, and training for farmers. This will help in maximizing growth rates and economic contributions for the purpose of sustainable regional development.